METODE PENGAJARAN BAHASA BALI DALAM TRADISI LISAN GENDING MAMANDA DI DESA ADAT KEDISAN KECAMATAN KINTAMANI KABUPATEN BANGLI - I Gede Mardi Yasa; Sentana, Gek Diah Desi; Arta, Putu Eddy Purnomo (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Kedisan Traditional Village is one of the Old Villages located in Kintamani District, Bangli Regency which is often referred to as Bali Aga Village or I Kraman Wingkang Ranu. Kedisan Traditional Village has various traditions, customs, culture, and dresta which are indeed passed down from generation to generation. Every inheritance of traditions in the village through various methods of its own. One of the traditions in the Kedisan Traditional Village is the oral tradition of gending mamanda. Gending mamanda is a type of sacred song sung by village women who are married and belong to the cluster of Let Village and Anyar Village, which number 185 people. This implementation is carried out at Dalem Pingit Temple when the ceremony and ceremony of the Nusaba ke-dasa are about to end or at the time of nganakin. But preceded by Mendak Ratu Puseh. Solving this problem by using descriptive qualitative methods with the type of method ex past facto. The preservation of Mamanda's music uses a learning method so that it remains sustainable in the midst of the onslaught of the globalization era. The methods used are the note-taking method, the reading method, and the listening method.